2012
DOI: 10.1007/s13566-012-0044-9
|View full text |Cite
|
Sign up to set email alerts
|

Content validation of the EORTC QLQ-BN20+2 with patients and health care professionals to assess quality of life in brain metastases

Abstract: Objective The validated EORTC quality of life (QOL) questionnaire QLQ-BN20 is a cancer subtype-specific supplement to the QLQ-C30 general QOL questionnaire for patients with primary brain neoplasms. The QLQ-C15-PAL core palliative questionnaire is an abbreviated version of the QLQ-C30 designed to decrease patient burden. We conducted content validation of the QLQ-BN20+2 for patients with brain metastases. Methods and materials Patients undergoing treatment for brain metastases, along with health care professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In this content validation study, feedback from patients and HCPs were based on methods previously used in a number of studies to examine content validity of QOL instruments [15][16][17]. The patient feedback indicated that the questionnaire was overall well received in this patient population.…”
Section: • • Hcps and Patients Combinedmentioning
confidence: 99%
“…In this content validation study, feedback from patients and HCPs were based on methods previously used in a number of studies to examine content validity of QOL instruments [15][16][17]. The patient feedback indicated that the questionnaire was overall well received in this patient population.…”
Section: • • Hcps and Patients Combinedmentioning
confidence: 99%
“…Of note, future uncertainty is a complex metric, arguably nonspecific for patients with brain metastases, highly situationally dependent (influenced by financial uncertainty and personal concerns even unrelated to the cancer diagnosis), and thus difficult to validate as a BN20 metric. 29 Thus, services aimed at financial toxicity or psychosocial concerns during cancer treatment could improve patient concerns noted by this QoL metric. 28 To minimize further adjustment of the FDR because of multiplicity of testing, we focused our analysis on the 9 main scales previously analyzed in other central nervous system tumor and brain metastases studies.…”
Section: Discussionmentioning
confidence: 99%
“…28 To minimize further adjustment of the FDR because of multiplicity of testing, we focused our analysis on the 9 main scales previously analyzed in other central nervous system tumor and brain metastases studies. [23][24][25][26][27][28][29][30] Notably, the EORTC phase III trial of WBRT versus observation reported significant changes in global health, physical function, and fatigue, with no clinically significant changes in the remaining QoL metrics. 30 A prospective study of the DEGRO QoL working group evaluated patients receiving SRS versus WBRT, and found that future uncertainty was the most prominent baseline metric among both arms (similarly reported by Caissie et al 23 ), which improved after SRS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations